Absolving the SSINS of Precision Interferometric Radio Data: A New Technique for Mitigating Faint Radio Frequency Interference. (7th October 2019) - Wilensky, Michael J.; Morales, Miguel F.; Hazelton, Bryna J.; Barry, Nichole; Byrne, Ruby; Roy, Sumit
Abstract: We introduce a new pipeline for analyzing and mitigating radio frequency interference (RFI), which we call Sky-Subtracted Incoherent Noise Spectra (ssins ). ssins is designed to identify and remove faint RFI below the single baseline thermal noise by employing a frequency-matched detection algorithm on baseline-averaged amplitudes of time-differenced visibilities. We demonstrate the capabilities of ssins using the Murchison Widefield Array (MWA) in Western Australia. We successfully image aircraft flying over the array via digital television reflection detected using ssins and summarize an RFI occupancy survey of MWA Epoch of Reionization data. We describe how to use ssins with new data using a documented, publicly available implementation with comprehensive usage tutorials.